The Need for A Character Education Management Model to Increase Students' Adversity Quotient in Elementary Schools - Wahira Siruwa; Sumarlin Mus; Abd Hamid (Yayasan Keluarga Guru Mandiri, 2023)
Adversity quotient is a cognitive, affective, and motor ability that is an important provision for someone to be able to navigate life. A good adversity quotient affects students' academic competence. This study aims to reveal the teacher's role in increasing the adversity quotient of students and the design form of developing a character education management model that teachers can use to increase the adversity quotient of students in elementary schools. The research method used the RD method in the preliminary stage. This research was conducted on school principals, teachers, and elementary school students. Sources of data were the school principal, teachers, and students through a questionnaire totaling 50 people. The results of the study show that: (1) An overview of students' adversity quotient that can be grown through character education is endurance, independence, self-control, focus, and critical thinking; (2) The teacher's role in increasing students' adversity quotient is not yet optimal, so it needs to get attention and time to implement properly; (3) The need for a character education management model that can be used by teachers starts from planning, implementing, and evaluating. The novelty of this research is the design of a character education management model that teachers can use to increase students' adversity quotient according to their needs and characteristics. This research is useful for teachers and students in elementary schools in increasing students’ adversity quotient. The benefits and significance of this character education management model can improve the quality and character of graduates.